Loss of the MAF Transcription Factor in Laryngeal Squamous Cell Carcinoma - Janiszewska Joanna; Bodnar Magdalena; Paczkowska Julia; Ustaszewski Adam; Smialek Maciej J; Szylberg Lukasz; Marszalek Andrzej; Kiwerska Katarzyna; Grenman Reidar; Szyfter Krzysztof; Wierzbicka Malgorzata; Giefing Maciej; et al. (MDPI, 2022)
MAF is a transcription factor that may act either as a tumor suppressor or as an oncogene, depending on cell type. We have shown previously that the overexpressed miR-1290 influences MAF protein levels in LSCC (laryngeal squamous cell carcinoma) cell lines. In this study, we shed further light on the interaction between miR-1290 and MAF, as well as on cellular MAF protein localization in LSCC. We confirmed the direct interaction between miR-1290 and MAF 3'UTR by a dual-luciferase reporter assay. In addition, we used immunohistochemistry staining to analyze MAF protein distribution and observed loss of MAF nuclear expression in 58% LSCC samples, of which 10% showed complete absence of MAF, compared to nuclear and cytoplasmatic expression in 100% normal mucosa. Using TCGA data, bisulfite pyrosequencing and CNV analysis, we excluded the possibility that loss-of-function mutations, promoter region DNA methylation or CNV are responsible for MAF loss in LSCC. Finally, we identified genes involved in the regulation of apoptosis harboring the MAF binding motif in their promoter region by applied FIMO and DAVID GO analysis. Our results highlight the role of miR-1290 in suppressing MAF expression in LSCC. Furthermore, MAF loss or mislocalization in FFPE LSCC tumor samples might suggest that MAF acts as a LSCC tumor suppressor by regulating apoptosis.